Contrast-enhanced ultrasonography could be a non-invasive method for differentiating none or mild from severe fibrosis in patients with biopsy proven non-alcoholic fatty liver disease. (1st September 2016) - Nasr, Patrik; Hilliges, Annette; Thorelius, Lars; Kechagias, Stergios; Ekstedt, Mattias
Abstract: Objective: The gold standard for diagnosing fibrosis stage in non-alcoholic fatty liver disease (NAFLD) is liver biopsy. The aim of this study was to determine whether contrast-enhanced ultrasonography (CEUS) with transit time measurements could be a non-invasive alternative for differentiating none or mild from severe fibrosis in NAFLD patients. Various serum markers and clinical variables were also evaluated. Materials and methods: Fifty-eight patients with NAFLD underwent CEUS prior to liver biopsy. All patients were also evaluated according to the Göteborg University Cirrhosis Index (GUCI), the AST-Platelet Ratio Index (APRI), the NAFLD fibrosis score, and the FIB-4 and BARD score. Results: The hepatic vein arrival time (HV) was shorter in patients with severe fibrosis (25.9 ± 4.8 vs 29.5 ± 4.7 s, p  = 0.023), and the difference between the hepatic and portal vein (ΔHV–PV) was shorter (2.3 ± 2.8 vs 6.4 ± 2.8 s, p  < 0.0001) while the difference in arrival time between the portal vein and hepatic artery (ΔPV-HA) arrival time was significantly longer (6.0 ± 2.2 vs 3.6 ± 1.6 s, p  < 0.0001). The area under receiver operating characteristics curve values for HV, ΔHV–PV and ΔPV–HA to separate none or mild from severe fibrosis was 0.71, 0.83 and 0.84, respectively. The corresponding figures for GUCI, APRI, NAFLD fibrosis score, FIB-4 and BARD score were 0.93, 0.92, 0.86, 0.90 and 0.77, respectively. Conclusions: CEUS and non-invasive scoring systems could exclude severe fibrosis in NAFLD patients.